(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – The purpose of this study is to investigate student motivation and gender differences in learning Spanish as a foreign language in the Malaysian context. Method – Student motivation was measured by means of a selfreport questionnaire based on Gardner’s social psychological model. The questionnaire contained both close-ended and open-ended questions to provide both quantitative and qualitative information. The participants consisted of 448 students from Universiti Kuala Lumpur Malaysian Spanish Institute where Spanish is a compulsory subject. Findings – The findings showed that the students were highly motivated toward learning Spanish. No significant differences were found between integrative and instrumental motivations and gender. Nonetheless, both quantitative and qualitative results suggested that the students were slightly more instrumentally inclined but simultaneously appreciated the target language and culture. This was particularly the case for the female students who showed significantly higher instrumental motivation in Spanish learning. Significance – The study supports the claim that motivation is context-specific and at the same time provides a better understanding of a Malaysian situated phenomenon. Its findings have underscored that different learning contexts have different impacts on student motivation. It is hoped that the understanding of Malaysian student motivation may contribute useful insights to improve the curriculum and instruction of foreign language learning.